EFEKTIVITAS MEKANISME TRANSMISI KEBIJAKAN MONETER JALUR HARGA ASET DI INDONESIA TAHUN 2016 - 2022 - Kezia Angel Pinaria; Harya Kuncara Wiralaga; Ari Saptono (CV. Denasya Smart Publisher, 2025)
The purpose of this research is to find out how effective the monetary policy transmission mechanism is on the asset price path in 2016-2022 in Indonesia by looking at how inflation responds to changes (shocks) given by related variables and how each transmission variable contributes to explaining the final target which is to stabilize the prices of goods and services that in this research describes through the inflation rate. The analysis method used is the Vector Error Correction Model (VECM) with Impulse Response Function (IRF) analysis and Forecast Error Variance Decomposition (FEVD). The effectiveness of the monetary policy transmission mechanism in this research can be seen from the results of the Impulse Response Function analysis which found that the variables that provided the longest shocks in influencing inflation were, respectively, the inflation variable, RBI7DRR, RPUAB, IHSG, then IPBIBS. Then, the results of the Forecast Error Variance Decomposition analysis found that the variable that made the biggest contribution in explaining inflation was the inflation variable itself, followed by RBI7DRR, IPBIBS, IHSG, and RPUAB.